2009
DOI: 10.1242/dev.032425
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism and pattern of yolk consumption provide insight into embryonic nutrition inXenopus

Abstract: Little is known about how metabolism changes during development. For most animal embryos, yolk protein is a principal source of nutrition, particularly of essential amino acids. Within eggs, yolk is stored inside large organelles called yolk platelets (YPs). We have gained insight into embryonic nutrition in the African clawed frog Xenopus laevis by studying YPs. Amphibians follow the ancestral pattern in which all embryonic cells inherit YPs from the egg cytoplasm. These YPs are consumed intracellularly at so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 45 publications
7
84
1
Order By: Relevance
“…The precursors of the yolk proteins, vitellogenins, are typically synthesized in organs distant from the gonad and are then endocytosed by the developing oocytes (Mosconi et al 2002;Tufail and Takeda 2009). Here they are stored in yolk platelets until they are degraded (Reimer and Crawford 1995;Jorgensen et al 2009). In C. elegans, the cathepsin L-like cysteine protease CPL-1 is involved in the degradation of yolk proteins during embryogenesis (Hashmi et al 2002;Britton and Murray 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The precursors of the yolk proteins, vitellogenins, are typically synthesized in organs distant from the gonad and are then endocytosed by the developing oocytes (Mosconi et al 2002;Tufail and Takeda 2009). Here they are stored in yolk platelets until they are degraded (Reimer and Crawford 1995;Jorgensen et al 2009). In C. elegans, the cathepsin L-like cysteine protease CPL-1 is involved in the degradation of yolk proteins during embryogenesis (Hashmi et al 2002;Britton and Murray 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Jorgensen et al [27] and ourselves [24] have shown that EP45 is not synthesized in oocytes but in the liver and that it is delivered to the oocytes via blood and, probably, via follicular cells. We also have shown that over-expression of EP45 does not induce meiotic maturation either in stage IV or VI oocytes.…”
Section: Comparison Between Proteomes Of Oocytes In Stage IV and Vimentioning
confidence: 96%
“…Indeed, a recent proteomic www.fhc.viamedica.pl study of yolk components in Xenopus laevis has shown that EP45 (under the new name of Seryp) is one of the major components of yolk granules and the major player in regulation of the source of energy necessary for embryo development [27]. On the basis of its amino acid sequence, EP45 was classified as a member of the serine protease inhibitors called Serpins [26,27]. EP45 has a histidine-rich N-terminus which determines its high affinity for nickel [28,29].…”
Section: Comparison Between Proteomes Of Oocytes In Stage IV and Vimentioning
confidence: 99%
“…Jorgensen et al [17] found a new class of proteins in Xenopus and named it seryp, which is a constituent of yolk protein massed in the yolk platelets. This protein acts as a signature protein of the yolk platelet as it is degraded earlier in the embryonic cells to provide nutrition.…”
Section: Introductionmentioning
confidence: 99%